Exploring Aachen minipigs as in vivo model for human intracranial studies: Focus on hind limb artery diameters - Lara Bender; Thorsten Sichtermann; Christoph Dorn; Jan Minkenberg; Andrea Stockero; Rebecca May; Hani Ridwan; Charlotte S. Weyland; Omid Nikoubashman; Martin Wiesmann; Christiane Franz (PLoS ONE, 2025)
Endovascular methods for stroke treatment have become increasingly popular in recent years and continue to be improved. Pigs serve as in vivo models in endovascular stroke research for device testing and training purposes. Due to a network of small vessels between the cerebral and intracranial arteries, called rete mirabile, catheterization of the brain-supplying arteries in pigs is impossible. Alternatively, various porcine arteries can be used. Aachen minipigs have become more popular in the last years, but specific data on their vascular diameters are limited to the forelimb arteries. Therefore, the aim of our study was to assess diameters of porcine hind limb arteries in eight female Aachen minipigs (weight of 47.08 kg ±  4.58 kg and age of 17 to 21 months), focusing on the internal iliac artery, external iliac artery, femoral artery, profunda femoris artery, popliteal artery, caudal tibial artery, cranial tibial artery, and sacral median artery, and to compare these diameters with diameters of human brain-supplying arteries. Measurements of artery diameters were conducted during experimental digital subtraction angiographies of a superordinate endovascular study. We found similarities between diameters of porcine hind limb arteries and human brain-supplying arteries: the porcine cranial tibial artery, sacral median artery, caudal tibial artery, popliteal artery, and profunda femoris artery are suitable for modelling human arteries. Our work may serve as a tool for planning and conducting interventional experiments involving Aachen minipigs and may therefore lead to reduced animal numbers according to the 3Rs (Replacement, Reducement, Refinement) from Russell and Burch.